If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 3 * 3) = 0 Multiply 3 * 3 (2x + 9) = 0 Reorder the terms: (9 + 2x) = 0 Remove parenthesis around (9 + 2x) 9 + 2x = 0 Solving 9 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 2x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 2x = 0 + -9 2x = 0 + -9 Combine like terms: 0 + -9 = -9 2x = -9 Divide each side by '2'. x = -4.5 Simplifying x = -4.5
| 2x+6=24-8x | | 4(e+2)-6=-3(e-3) | | 1.5=.05x-1935 | | -0.35x=2.1 | | x+(2x+0.16)+(x+0.06)=1.4 | | 7=9+c | | (x+3)*2= | | 57-5x=31x+17 | | -s+7-(-1-3s)= | | lnx=-1.9 | | 9-9x=77-23x | | 1.5+98.35=.05x | | 0.3t-5=0.5t+1 | | y-6.5=8.2 | | x-7.8=6.53 | | y+5x+4x+5x=360 | | 16+3v=6v | | 0=-.004x^2+x+2.5 | | 2x^2+10x+7=0 | | 0.3t-5=0.5+1 | | 3ab-4b+5ab+4b= | | 10m=12 | | 4x^3+20x^2-68x-84=0 | | 15x-y+5(3x-2y+5z)= | | (2x+1)(x+4)=0 | | 10m-6=12 | | 6x^2-5s-6=0 | | n=0.05x-98.35 | | 10m-12=12 | | 3(r+2)=4(r-1) | | 8(4)=-3m+1 | | 3(x+3)=x+8 |